A Case Report of Vascular Ectasias of GI Tract Presenting as Occult Gastro-Intestinal Bleed Diagnosed on Capsule Endoscopy - Hajare, Santosh; M, Suhas (Journal of Medicine, 2020)
Abstract Not Available J MEDICINE JUL 2020; 21 (2) : 117-118